Implementation of Ecological Messages in Prophetic Hadiths for Environmental Education in Cirebon: Realizing the Climate City Program Based on Nubuwwah Values - Muslihudin, Muslihudin; Muthi’ah, Anisatun; Iskandar, Amin; Febriyanto, Alfian (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This study analyzes the actualization of environmental hadith in the success of the Cirebon climate city program through mitigation and adaptation efforts due to climate change. Religion plays a vital role in mitigation and adaptation efforts due to climate change, however, it is often overlooked. The research problem in this study is how environmental hadith is actualized to make the Cirebon climate city program successful through mitigation and adaptation efforts due to climate change. This research uses qualitative methods. The unit of analysis is the community that actualizes environmental hadith in the success of the Cirebon climate city program. Informants were selected using purposive techniques such as clerics, students, environmental activists, Proklim residents, and the government. Data were collected using observation, interview, and documentation techniques. Data sources are primary and secondary. Data analysis is processed using triangulation techniques. The results showed that environmental hadiths were actualized in the success of the Cirebon climate city program. The actualization of environmental hadith is manifested in various social movements based on environmental justice carried out by both the government and the community, such as the climate village program (proklim) which is spread across various locations in the city of Cirebon. Institutions/organizations as well as religious actors/agents are inspired and motivated to carry out social movements due to hadiths about the environment. This study concludes that the environmental crisis in Cirebon City forces all elements of society and the government to mitigate and adapt to climate change. One of the mitigation and adaptation efforts due to climate change in Cirebon City is the climate village program (Proklim) in 15 different locations. Hadith has a very important influence on the implementation of the Cirebon City climate village program (Proklim) in efforts to mitigate and adapt to climate change.